Dietary Management of a Patient with Both Maple Syrup Urine Disease and Type I Diabetes - Mehmet Gündüz; Nevra Koç; Özlem Ünal; Seyit Ahmet Uçaktürk (Galenos Yayinevi, 2018)
Maple Syrup Urine disease (MSUD) is caused by the deficiency of the branched chain 2-ketoacid dehydrogenase complex. Type I diabetes mellitus (TIDM) is a chronic illness characterized by the body's inability to produce insulin due to the autoimmune destruction of the beta cells in the pancreas. A case with both MSUD and TIDM has not been reported previously. In this study, we presented a patient with both MSUD and TIDM, dietary management and the follow up period. Dietary management could be difficult in the presence of two disorders affecting more than one macronutrient component such as both carbohydrate and protein. Our patient had good metabolic control in the follow-up period. Treatment was successful with intensive insulin, frequent feeding and a leucine restricted diet.